2018
DOI: 10.3390/rs10101543
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and Intercomparison of High-Resolution Satellite Precipitation Estimates—GPM, TRMM, and CMORPH in the Tianshan Mountain Area

Abstract: With high resolution and wide coverage, satellite precipitation products like Global Precipitation Measurement (GPM) could support hydrological/ecological research in the Tianshan Mountains, where the spatial heterogeneity of precipitation is high, but where rain gauges are sparse and unevenly distributed. Based on observations from 46 stations from 2014–2015, we evaluated the accuracies of three satellite precipitation products: GPM, Tropical Rainfall Measurement Mission (TRMM) 3B42, and the Climate Predictio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 66 publications
9
47
0
Order By: Relevance
“…Crossing national boundaries of China and Kyrgyzstan, the range located in China is known as the "Eastern Tianshan" approximately 1,700 km in length and the outside range is so called "Western Tianshan" (Figure 1). Studies from water isotope measurements (Aizen et al, 1996;Aizen et al, 2006;Kreutz et al, 2003) and modeling approaches (Keys et al, 2014;Sun & Wang, 2014;Zhang et al, 2018) suggest a number of moisture sources for the Tianshan mountains area (Baldwin & Vecchi, 2016). Moisture follows the westerlies from Aral, Caspian, Black Sea, and Mediterranean as well as the Atlantic Ocean, all the way to the mountains particularly on the west side.…”
Section: Tianshan Mountainsmentioning
confidence: 99%
See 1 more Smart Citation
“…Crossing national boundaries of China and Kyrgyzstan, the range located in China is known as the "Eastern Tianshan" approximately 1,700 km in length and the outside range is so called "Western Tianshan" (Figure 1). Studies from water isotope measurements (Aizen et al, 1996;Aizen et al, 2006;Kreutz et al, 2003) and modeling approaches (Keys et al, 2014;Sun & Wang, 2014;Zhang et al, 2018) suggest a number of moisture sources for the Tianshan mountains area (Baldwin & Vecchi, 2016). Moisture follows the westerlies from Aral, Caspian, Black Sea, and Mediterranean as well as the Atlantic Ocean, all the way to the mountains particularly on the west side.…”
Section: Tianshan Mountainsmentioning
confidence: 99%
“…And as the first mountain system barrier confronting northern air masses moving into central Asia, the Tianshan mountains area affect the climatic processes occurring in northern central Asia, similar to that of the Himalayas to the south (Aizen et al, 1997). Due to its unique long latitudinal distribution and significant hydrothermal pattern adjustment for central Asia and for the world, there are lots of climatological (Baldwin & Vecchi, 2016;Cai et al, 2019;Zhang et al, 2009), ecological (Han et al, 2016;Zhang et al, 2013), and hydrological (Hagg et al, 2007;Zhang et al, 2018) studies focusing on the Tianshan mountains area.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that the GPM products have improved in terms of detection rate and detection accuracy to a certain degree compared with TRMM in different geographic locations, such as the tropics (Tan & Duan, 2017; Tan & Santo, 2018), the subtropics (Z. Wang et al, 2017), and the midlatitude regions (Gebregiorgis et al, 2018; Tang et al, 2016) and with different underlying surface condition, such as in high mountain area (C. Zhang, Chen, et al, 2018), basin area (Jiang et al, 2018), plateau (S. Zhang, Wang, et al, 2018), and coastal area (Kim et al, 2017). In particular, the IMERG products are superior to TMPA in detecting precipitation of weak to moderate intensity (Muhammad et al, 2018; C. Zhang, Chen, et al, 2018). Compared to the TRMM, the GPM significantly widens the spatial coverage of the observations (from 35° to 65°), improves the detection accuracy of weak precipitation and snowfall processes (Ku band at 13.6 GHz and Ka band at 35.5 GHz), and boosts the ability to distinguish and identify liquid‐state and solid‐state precipitation (GPM Microwave Imager at 165.5 and 183.3 GHz) (Hou et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…IMERG products have not been widely applied in meteorological or hydrological fields, and presently, several studies tend to concentrate on evaluating data reliability. Many studies have evaluated the application of IMERG‐F at different spatiotemporal scales (Asong et al, 2017; H. Guo et al, 2016; Mahmoud et al, 2019; Reddy et al, 2019; Tang et al, 2016; Wei et al, 2018) under different topographic and climate characteristics (Kim et al, 2017; C. Zhang, Chen, et al, 2018; Lu et al, 2019, 2018; Anjum et al, 2019), and in the hydrological field (Jiang et al, 2018; Ma et al, 2019; N. Li, Tang, et al, 2017; Z. Wang et al, 2017). According to reference standards such as ground rain gauges or weather radar inversion products (e.g., quantitative precipitation estimation) (N. Li, Wang, et al, 2017), these studies evaluate IMERG‐F solely or in conjunction with other satellite‐based precipitation data analysis products (e.g., TMPA, CMORPH, and Precipitation Estimation from Remotely Sensed Information using Artificial Neural Networks).…”
Section: Introductionmentioning
confidence: 99%
“…The accuracy of precipitation data has been validated in various areas (Jiang & Bauer-Gottwein, 2019;Tan & Duan, 2017;Tang et al, 2016) prior to further comparative studies with the TRMM products. Zhang, Chen, et al (2018) indicated that GPM outperformed TRMM in estimating daily precipitations over the Tianshan mountain range, China. showed that the enhancement of IMERG over TRMM is more significant at the 3-hr scale than at the daily scale in Guangdong Province, China.…”
Section: Introductionmentioning
confidence: 99%